Abnormally adherent and invasive placenta: A spectrum disorder in need of a name - Collins, SL; Chantraine, F; Morgan, TK; Jauniaux, E (Wiley, 2017)
There is little doubt that the worldwide caesarean delivery epidemic has led to an increased incidence of abnormally adherent and invasive placentation (AAIP). The significant impact that this disorder has on maternal morbidity and mortality has led to a flurry of publications in the world literature concerning all aspects of this condition. These papers have arisen from many sources notably pathologists, epidemiologists, obstetricians, and radiologists. Subsequently, the disjointed terminology used to describe this complex disorder is becoming increasingly confusing and perhaps misleading. In their review, Bhide et al. call for standardisation of the diagnostic terminology[1]. We agree this is necessary if we are to better understand, diagnose and manage this complex condition.